2021
DOI: 10.4274/tnd.2021.04820
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Sleep Quality in Healthcare Workers as Part of the COVID-19 Outbreak

Abstract: Objective:We aimed to evaluate the sleep quality and affceting factors of the healthcare professionals working in our hospital during the coronavirus disease-2019 (COVID-19) pandemic. Materials and Methods: One hundred fifty-two healthcare professionals, 95 females and 57 males working during the COVID-19 pandemic, were included in our study. In the study, the factors affecting sleep quality were statistically evaluated by using the patients' demographic features, the Pittsburgh Sleep Quality Index (PSQI), Fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…Regarding the administered sleep measures, 103 studies reported PSQI scores. Specifically, 100 reported PSQI global scores [ [37] , [38] , [39] , [40] , 42 , 43 , 45 ], [ 46 , [48] , [49] , [50] , [51] , [52] , [53] ], [ [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [65] , [66] , [67] , [68] ], [ [70] , [71] , [72] , [73] , 75 , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , 86 , 87 ], [ [91] , [92] , [93] , [94] , [96] , [97] , [98] , 102 , 103 , [106] , [107] , [108] , [109] , [110] ], [ [113] , [114] , [115] , [116] , 119 , 120 , [122] , [123] , [124] , [...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the administered sleep measures, 103 studies reported PSQI scores. Specifically, 100 reported PSQI global scores [ [37] , [38] , [39] , [40] , 42 , 43 , 45 ], [ 46 , [48] , [49] , [50] , [51] , [52] , [53] ], [ [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [65] , [66] , [67] , [68] ], [ [70] , [71] , [72] , [73] , 75 , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , 86 , 87 ], [ [91] , [92] , [93] , [94] , [96] , [97] , [98] , 102 , 103 , [106] , [107] , [108] , [109] , [110] ], [ [113] , [114] , [115] , [116] , 119 , 120 , [122] , [123] , [124] , [...…”
Section: Resultsmentioning
confidence: 99%
“… Author Country Sample (n) Female Age Type of pop. Measure NOS Abbas et al, 2021 [ 37 ] Kuwait 217 0.44 x̄ = 35.8y health w. PSQI gen-sub 5 Abid et al, 2021 (a) [ 38 ] Tunisia 48 1 x̄ = 8.66y children PSQI gen 5 Abid et al, 2021 (b) [ 38 ] Tunisia 52 0 x̄ = 8.66y children PSQI gen 5 Akıncı and Başar, 2021 [ 39 ] Turkey 152 0.63 x̄ = 35.8y health w. PSQI gen-sub 5 Akkuş et al, 2021 [ 40 ] Turkey 595 0.66 x̄ = 27.9y general PSQI gen 6 Al Maqbali, 2021 [ 41 ] Oman 987 0.91 >18y health w. PSQI sub 5 Al-Musharaf et al, 2021 [ 42 ] Saudi Arabia 297 1 x̄ = 20.7y general PSQI gen 5 Alfonsi et al, 2021 (a) [ 43 ] Italy 72 1 x̄ = 35.68y general PSQI gen-sub 6 Alfonsi et al, 2021 (b) [ 43 ] Italy <...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors such as fear of contagion, fear of pandemic, and loneliness put healthcare workers' physical and psychological health at risk. 8 This psychological burden causes fatigue symptoms to aggravate various psychological problems among nurses. It has been reported that a decrease in nurses' resistance to physical, mental, and emotional stress will result in anxiety, depression, and fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…8 The effects of COVID-19 on health workers not only include consequences such as depression but also sleep problems during the pandemic since workers had to adapt to new work protocols characterized by a higher-than-usual work intensity. 9 Although poor sleep quality can be the consequence of various sleep disorders, such as insomnia, apnea, etc., it can also be related to symptoms of depression and anxiety. 10 In addition, since sleep is necessary for the homeostasis of the immune system, the decrease in sleep quality of health personnel can negatively alter their emotional and physiological state, allowing in turn the activation of inflammatory processes, the release of cytokines and increased susceptibility to depressive disorders.…”
Section: Introductionmentioning
confidence: 99%